Space operations : experience, mission systems, and advanced concepts - Schmidhuber, Michael; Cruzen, Craig; Kehr, Joachim (Progress in astronautics and aeronautics, 2013)
"A collection of materials presented at the 12th SpaceOps Conference, held in Stockholm, Sweden in June 2012. From the almost 300 papers presented and discussed at the conference, those selected for this volume represent a cross section of three main subject areas: Mission Preparation and Management - mission design, development, and planning; Data and Communications - the infrastructure needed on the ground, from antennas to software, in order to communicate with and retrieve data from spaceborne resources; and Mission Execution - a focus on the aspects of specific space missions during preparation for flight and throughout operations. All of the selected papers exemplify the SpaceOps organization's goal of presenting and discussing the current state of space operations and the most recent developments in the field."--Publisher description